A BIM-integrated Fuzzy Multi-criteria Decision Making Model for Selecting Low-Carbon Building Measures. (2015) - Chen, L.; Pan, W.
Abstract: Low-carbon building (LCB) has been regarded as an innovative and practical approach to reducing building carbon emissions. The design decision-making for LCBs should consider various criteria which however are often associated with uncertain information. Little research has examined multi-criteria decision making (MCDM) in selecting LCB measures, particularly in high-density subtropical urban environments. That selection process is inhibited by the lack of consensus on assessing the performance of LCB options and of an efficient decision support system. The aim of this paper is to develop a BIM-integrated fuzzy MCDM model for selecting LCB measures. The paper identifies the key criteria and alternatives to systematically assess LCB measures. Five criteria and nine alternatives were identified within the context of high-rise commercial buildings in Hong Kong, which are centralized on technical, economic and environmental aspects of building performance. With the use of BIM and eQUEST, a MCDM model based on Fuzzy PROMETHEE is developed. The developed model is validated utilizing a real project case in Hong Kong. The results will provide design decision-makers with a consolidated tool for selecting LCB measures.